DNAzyme Hybridization, Cleavage, Degradation and Sensing in Undiluted Human Blood Serum - Zhou, Wenhu; Chen, Qingyun; Huang, Po-Jung Jimmy; Ding, Jinsong; Liu, Juewen (American Chemical Society, 2015)
RNA-cleaving DNAzymes provide a unique platform for developing biosensors. However, a majority of the work has been performed in clean buffer solutions, while the activity of some important DNAzymes in biological sample matrices is still under debate. Two RNA-cleaving DNAzymes (17E and 10-23) are the most widely used. In this work, we carefully studied a few key aspects of the 17E DNAzyme in human blood serum, including hybridization, cleavage activity, and degradation kinetics. Since direct fluorescence monitoring is difficult due to the opacity of serum, denaturing and nondenaturing gel electrophoresis were combined for studying the interaction between serum proteins and DNAzymes. The 17E DNAzyme retains its activity in 90% human blood serum with a cleavage rate of 0.04 min–1, which is similar to that in the PBS buffer (0.06 min–1) with a similar ionic strength. The activity in serum can be accelerated to 0.3 min–1 with an additional 10 mM Ca2+. As compared to 17E, the 10-23 DNAzyme produces negligible cleavage in serum. Degradation of both the substrate and the DNAzyme strand is very slow in serum, especially at room temperature. Degradation occurs mainly at the fluorophore label (linked to DNA via an amide bond) instead of the DNA phosphodiester bonds. Serum proteins can bind more tightly to the 17E DNAzyme complex than to the single-stranded substrate or enzyme. The 17E DNAzyme hybridizes extremely fast in serum. With this understanding, the detection of DNA using the 17E DNAzyme is demonstrated in serum.
This document is the Accepted Manuscript version of a Published Work that appeared in final form in Analytical Chemistry, copyright © American Chemical Society after peer review and technical editing by publisher. To access the final edited and published work see http://dx.doi.org/10.1021/acs.analchem.5b00220.
Keywords: DNAzyme Hybridization; Cleavage; Degradation; Human Blood Serum